Influence of loopback interference channel in energy harvesting full-duplex relaying network over block rayleigh fading channel: performance analysis - Phu Tran Tin; Van-Duc Phan; Le Anh Vu (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The main idea of this paper is to investigate the system performance (SP) ofenergy harvesting FD relaying network over block rayleigh fading channelunder the influence of the loopback interference channel. In the first stage,we proposed the system modeland analyzed the energy harvesting and theinformation transmission phases. Furthermore, the mathematical form for theoutage probability (OP) is analyzed and derived in two kinds of loopbackinterference: residual self-interference is modeled as AWGN vàresidual self-interference is still a random variable. All the mathematical, analyticalexpressions are verified using the Monte Carlo simulation.